Vegetation Classification and Habitat Types of Gambella National Park - Gatluak Rolkier; Kumelachew Yeshitela (International Journal of Forestry Research)
Gambella National Park has a diverse set of habitat types which Ethiopia shares with its neighbor, South Sudan, and the park is considered as one of the top wildlife areas of Ethiopia. The objectives of this research were to determine vegetation types and identify habitat types on recent satellite imageries. The method used for vegetation data collection was transects lines. PC-ORD software was used for analyzed vegetation data while Rapid Eye image 5 m resolution 2012 was analyzed by ArcGIS version 10.1 to classify the habitats map of Gambella National Park. The cluster analysis classified the Gambella National Park into 6 vegetation communities, and the relative abundance and relative frequency were used for naming vegetation community types. However, the satellite image had classified the Gambella National Park into 5 major habitat types.